The Effect of the Saudi-Iranian agreement on the conflict in Yemen (قضايا سياسية, 2024)
The study addressed the limitation of the Saudi-Iranian agreement on the conflict in Yemen, which has been signed on 10 March 2023. This agreement is deeply important for the Saudi and Iran relations that may be a step to their rapprochement as well as for the Arab region, particularly in this period due to the Saudi-Iranian relations interruption since 2016 and the context of Arab region that many events have taken place since 2011 which was known as Arab spring. As far as Yemeni conflict is concerned which is still ongoing, many questions emerged as to whether the agreement might have positive effects on the conflict in Yemen or not? Questions like these to be answered, The limitation of agreement whether the level of the Saudi and Iran or the level of the international alliances context should be studied, as well as Yemeni conflict that related to the actors and conflict issues, and this will explain the limitation of the Saudi-Iranian agreement on the conflict in Yemen.